PENGARUH PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI IPA SMA YPPGI WAMENA KABUPATEN JAYAWIJAYA - Kayame, Marthinus; Kho, Ronaldo (Magister Pendidikan IPA, UNCEN, 2014)
The aim of this research to know the influence of: 1) Cooperative Learning Tipe Make A Match Mathematics learning achievement, 2) Learning motivation in achievement Mathematics learning, dan 3) Cooperative Type Make A Match and learning all together to student achievement. The research program is 516 students of YPPGI Senior High School in Jayawijaya regency and as a research sample collection instrument for all variable using Likert data scale. The instrument of research is using to collect the research data to try before, to continuing with validy and reliability data. To count this data using SPSS 16,0 program the hypothesis test on this research was using a simple technic correlation and double regre with helped by SPSS 16,0. Based on hypothesis can be summarized that: 1) The learning of cooperative tipe Make A Match to influence to product of mathematics learning, 2) The motivation in learning can influence in achievement mathematics learning, 3) Learning cooperative tipe Make A Match and learning motivation as together to influence to student learning mathematics achievement to student of XI IPA YPPGI Senior High School YPPGI in Jayawijaya regency. Key words: Learning Types, Type of Make A Match, Study motivation, sucses study of mathematics subject.